B282 Audit of the epidural analgesia service at the central delivery suite, mater dei hospital, Malta. (11th August 2022) - Galea, R; Drake, M; Schembri, N; Buhagiar, G; Abela, GP; Attard Cortis, PM
Abstract : Background and Aims: Mater Dei Hospital in Malta provides a 24-hour neuraxial analgesia service in its delivery suite. The Royal College of Anaesthetists (RCoA) recommends that in such set-ups, an anaesthetist should attend to labouring women within 30 minutes of request, and in exceptional cases, within one hour [1] . Other standards of care include a re-siting rate of <15% and an accidental dural puncture (ADP) rate of <1% [1] . The aim of this audit was to examine these standards in our unit. Methods: After ethical approval, data was collected retrospectively over four weeks from September to October 2021, looking at time of call to the anaesthetist, time of test dose administration, re-siting rates, and number of ADPs. The time interval from the call to time of test dose administration served as a surrogate to the actual waiting time. Data was inputted and analysed using MS Excel spreadsheet. Results: A total of 86 parturients requested epidural analgesia out of a total 345 deliveries (25%). The average time from request to administration of test dose was 34 minutes. Average maternal age was 30.5 years, 3.5% required re-siting of their epidural catheter and there were no ADPs. Conclusions: Using the surrogate marker, the average epidural waiting time was surmised to be within the recommended RCoA standard as were the epidural re-siting and ADP rate. This may be limited by the relatively short period of time the study was carried out over. Epidural analgesia remains the gold standard to manage labour pain and so our results are both satisfactory and encouraging.